2001
DOI: 10.1093/qjmed/94.4.187
|View full text |Cite
|
Sign up to set email alerts
|

Why is there so much end-stage renal failure of undetermined cause in UK Indo-Asians?

Abstract: There is a high incidence of end-stage renal failure (ESRF) of undetermined cause in the Indo-Asian population of the UK. We studied patients presenting from the district of Brent and Harrow, which has a large Indo-Asian community, and whose renal services are largely provided by our centre. The diagnosis and ethnicity of patients starting renal replacement therapy and/or undergoing renal biopsy were collated. The incidences of ESRF, rates of renal biopsy and underlying diagnoses were calculated for Indo-Asian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 0 publications
1
26
1
Order By: Relevance
“…Our findings of similar AER and prevalence of MA in UK South Asians and Europeans confirm those of UKPDS (17) in people with type 2 diabetes but do not correspond with the high rates of ESRD in South Asians (28) or the findings of Mather et al (14) and Fischbacher et al (15). The last two studies were smaller than ours.…”
Section: Comparison With Other Studiescontrasting
confidence: 58%
See 2 more Smart Citations
“…Our findings of similar AER and prevalence of MA in UK South Asians and Europeans confirm those of UKPDS (17) in people with type 2 diabetes but do not correspond with the high rates of ESRD in South Asians (28) or the findings of Mather et al (14) and Fischbacher et al (15). The last two studies were smaller than ours.…”
Section: Comparison With Other Studiescontrasting
confidence: 58%
“…However, in the United Kingdom, in those with diabetes, South Asians are known to have a 13-fold increase in risk for ESRD compared with Europeans (30), and in those without diabetes, South Asians have a 3.5-fold increase in risk (28,30,31). A large US primary care study of people with diabetes found that those of Asian origin without hypertension had two-fold prevalence of microalbuminuria (32).…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent renal biopsy study reports increases in most patterns of parenchymal renal disease, including chronic interstitial nephritis of undetermined cause. 6 There is a marked excess of tuberculosis among South Asians with renal failure; anecdotal evidence suggests tuberculosis as a possible aetiological agent for this non-specific chronic renal disease, with occasional impressive improvements in renal function in response to anti-tuberculous therapy even in the absence of positive microbiological evidence or characteristic renal histology. But cause and effect have not been systematically confirmed.…”
Section: Non-diabetic Renal Failurementioning
confidence: 99%
“…This different genetic heritage should be reflected, in the case of diabetes complications, in different rates of complications. There are now numerous studies that suggest the incidence of renal complications of diabetes is significantly different in diverse racial or ethnic groups even when they reside in the same country [8][9][10][11][15][16][17][18][19].…”
Section: Renal Diseasementioning
confidence: 99%